Firm characteristics, business environment, strategic orientation, and performance - Sofik Handoyo; Sri Mulyani; Erlane K. Ghani; Slamet Soedarsono (Administrative Sciences, 2023)
The purpose of this study is to empirically examine the influence of firm characteristics (size, age, industry type, and ownership) on a firm's strategic orientation. The business environment, namely market uncertainty and competition intensity, is also analysed in association with the firm's strategic orientation. Furthermore, the implication of strategic orientation for performance is tested. The study used 1024 data sets of 128 manufacturing firms listed on the Indonesia stock exchange from 2014 to 2021. Data panel regression and independent t-tests were employed for statistical analysis. Adopting Miles and Snow's strategy typology framework, the findings indicated that the firm size, industry type, and competition intensity significantly influence the firm's strategic orientation. Small firms preferred to adopt a proactive strategic orientation (prospector and analyser). Firms in the fast-moving consumer goods (FMCG) industry tended to adopt a proactive strategic orientation (prospector and analyser). Strategic orientation was found to positively and significantly influence firm performance. Firms that adopt a proactive strategic orientation (analyser and prospector) showed better performance than defensive ones (reactor and defender).
Keywords: 350; business environment; firm characteristics; manufacturing; performance; strategic orientation